2014
DOI: 10.1109/tasc.2014.2318316
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting Tunnel Junction Detectors for Analytical Sciences

Abstract: Superconducting tunnel junction (STJ) detectors exhibit superior detection performance for photons and particles at a high spectroscopic resolution of ∼10 eV, a short dead-time (decay time) of ∼μs, a high quantum efficiency of ∼100%, and a low detection threshold energy of less than 1 eV, which cannot be achieved by conventional detectors. The outstanding detection performance originates from a small superconducting energy gap of ∼meV, which is three orders of magnitude smaller than ∼eV in semiconductors. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…The hydrogen yield was higher than the theoretical maximum of 4.92 wt %, plausibly due to gaseous contaminants, including carbon monoxide and carbon dioxide, produced by the thermal decomposition of OA at temperatures higher than 100 °C (see Figure S3b). Note that dry hydrolysis of the SB/OA•2H 2 O 44 Figure 5c displays the TCD response to the gaseous products generated by the dry hydrolysis of the SB/OA•2H 2 O composite. The TCD response to hydrogen gas was calibrated with 5, 10, and 30% hydrogen references, and the results showed that the gas products obtained by the dry hydrolytic dehydrogenation of the composite contained mostly pure hydrogen and a small portion of Ar gas without harmful gases that can potentially poison the PEMFC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrogen yield was higher than the theoretical maximum of 4.92 wt %, plausibly due to gaseous contaminants, including carbon monoxide and carbon dioxide, produced by the thermal decomposition of OA at temperatures higher than 100 °C (see Figure S3b). Note that dry hydrolysis of the SB/OA•2H 2 O 44 Figure 5c displays the TCD response to the gaseous products generated by the dry hydrolysis of the SB/OA•2H 2 O composite. The TCD response to hydrogen gas was calibrated with 5, 10, and 30% hydrogen references, and the results showed that the gas products obtained by the dry hydrolytic dehydrogenation of the composite contained mostly pure hydrogen and a small portion of Ar gas without harmful gases that can potentially poison the PEMFC.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The single peak shown at t R = 1.545 min owing to the flow of the air is either commonly observed in SB/OA·2H 2 O or the air undergoes dry hydrolysis. The peaks assigned to the three most abundant gases in the atmosphere, that is, N 2 ( m / z = 28.1), O 2 ( m / z = 32.1), and Ar ( m / z = 40.1) peaks are clearly observed with small percentages of N ( m / z = 14), O ( m / z = 16), and H 2 O ( m / z = 18) …”
Section: Resultsmentioning
confidence: 99%
“…This can be explained by the difficulty to measure additional physical quantities, while preserving the existing high performances of current APT instruments (Da Costa et al, 2012). Recent developments of position-energy-sensitive detectors (PESDs) greatly compounds this difficulty (Funsten et al, 2004;Buhr et al, 2010;Ohkubo et al, 2014;Fujii et al, 2015), where it can be stated that existing arrays of energy-sensitive cells introduce a very slow response time, that does not go below hundreds of nanoseconds, which is a longway from the few nanoseconds required in APT experiments. This limitation should have the effect of restricting the detection rate and the multi-hit capability of APT instruments.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Nb/Al/AlO x /Al/Nb junctions, as shown in Fig. 1, are used in X-ray or terahertz detectors because of their low leakage features [3]. The top Al layer is expected to suppress not only the creation of metallic channels in the AlO x insulator, but also to suppress the growth of lower valence niobium oxides on the AlO x because of the chemical reaction between the Nb and AlO x during the deposition of the top Nb electrode.…”
Section: Introductionmentioning
confidence: 99%